2021
DOI: 10.3389/fmed.2021.735590
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of BCG Therapy Targeting Neutrophil Extracellular Traps, Autophagy, and miRNAs in Bladder Cancer: Implications for Personalized Medicine

Abstract: Bladder cancer (BC) is the ninth most common cancer and the thirteenth most common cause of mortality worldwide. Bacillus Calmette Guerin (BCG) instillation is a common treatment option for BC. BCG therapy is associated with the less adversary effects, compared to chemotherapy, radiotherapy, and other conventional treatments. BCG could inhibit the progression and recurrence of BC by triggering apoptosis pathways, arrest cell cycle, autophagy, and neutrophil extracellular traps (NETs) formation. However, BCG th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 168 publications
2
5
0
Order By: Relevance
“…Inflammatory factors and microbial pathogenic factors activate neutrophils by stimulating the autophagy pathway and NET release. 216 Our team also confirmed that RA patients with joint fluid had significantly higher levels of neutrophil autophagy than peripheral blood neutrophils. 217 Previous studies have shown that autophagy-related light chain 3 (LC3) protein expression is upregulated in neutrophils isolated from RA synovial fluid when lysosomal pH in neutrophils is decreased or cells are exposed to chloroquine (CQ) and small interfering RNA (siRNA) Atg5 transfection.…”
Section: Enhanced Neutrophil Autophagy Associated With Various Autoim...supporting
confidence: 55%
“…Inflammatory factors and microbial pathogenic factors activate neutrophils by stimulating the autophagy pathway and NET release. 216 Our team also confirmed that RA patients with joint fluid had significantly higher levels of neutrophil autophagy than peripheral blood neutrophils. 217 Previous studies have shown that autophagy-related light chain 3 (LC3) protein expression is upregulated in neutrophils isolated from RA synovial fluid when lysosomal pH in neutrophils is decreased or cells are exposed to chloroquine (CQ) and small interfering RNA (siRNA) Atg5 transfection.…”
Section: Enhanced Neutrophil Autophagy Associated With Various Autoim...supporting
confidence: 55%
“…Autophagy is a tumor-suppressive mechanism that maintains genomic integrity and suppresses tumorigenesis ( 60 , 61 ), as occurs with RAC3 knockdown cells. Activation of PI3K/AKT/mTOR, an important pathway regulating autophagy, is prevalent in many cancers and may be responsible for reducing cytoprotective autophagy and deregulated proliferation ( 62 ). Studies have confirmed that targeting autophagy in combination with other treatment strategies is generally more effective than monotherapy ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…In-depth exploration of these complex mechanisms, exploiting the chemical modulators currently available for blocking or triggering these cell death methods is essential to treat cancer, infectious diseases, and autoin ammatory by promoting the development of precise therapeutic targets 70 . Some RCD types have been found to correlate to multiple chemotherapeutic drugs in treating bladder cancer [78][79][80][81] . However, few mechanism studies were performed on RCD types in bladder cancer 82 .…”
Section: Discussionmentioning
confidence: 99%